Ibn Khaldun's Thoughts On Production In The Islamic Economic System - Nurhaerana, Nurhaerana; Mahsyar, Mahsyar; Damirah , Damirah (Economos : Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this study is to provide an explanation of the concept of production according to Ibn Khaldun in the Islamic economic system and its contribution to Islamic economics. This type of research is literature research. The results of this study will be described in the form of text analysis. The approach in this study is to use historical, philosophical and Islamic economic approaches. The primary data in this study are data from books that refer to Ibn Khaldun's thoughts on production in research. Likewise other data related to the subject of research, both the results of documentation and the results of documentation. The results of this study are prepared with stages of orientation, exploration, focused study and conclusions. The conclusion of the study shows that production in Ibn Khaldun's thought is part of sustenance that has so much urgency in economic activity to manage natural resources with effort and hard work from human hands in the production process to meet the needs of human life. Furthermore, in the perspective of Islamic economics, production is part of sustenance in building an Islamic economic system with the foundation of the Qur'an and al-hadith in every production process in economic activity. The last is the contribution of production in the Islamic economic system related to sustenance which aims at the benefit of the community in worshiping and seeking the pleasure of Allah Almighty.